Comparison of the efficacy of two hand decontamination methods: Alcoholic septicidine and povidone–iodine solutions - Nooshin Bazzazi; Hamidreza Ghasemi Basir; Roya Najafi Vosough; Fatemeh Eslami; Negar Akbarzadeh (PLoS ONE, 2025)
Background and aim Surgical site infections (SSIs) are a critical concern in ophthalmic surgical settings, where rigorous hand hygiene is essential to prevent postoperative complications. This study aimed to compare the efficacy of two antiseptic agents, Septicidine and Betadine, in reducing bacterial contamination on the hands of surgical staff. Methods Thirty ophthalmic surgeons and operating room personnel participated in the study. The participants scrubbed their hands with either Septicidine (alcohol-based antiseptic) or Betadine (iodine-based antiseptic). Bacterial cultures were obtained before and after hand scrubbing. The presence of bacteria, including antibiotic-resistant strains, was assessed and compared between the two groups over a four-month period at Sina Hospital in Hamadan. Results A total of 120 hand culture samples were collected. Both antiseptics significantly reduced bacterial contamination. However, residual bacterial growth was observed in 8 out of 120 Septicidine samples and 10 out of 120 Betadine samples. Although Septicidine showed a slightly lower rate of residual contamination, the difference was not statistically significant (P = 0.624). The most commonly isolated organisms were Staphylococcus species, some of which exhibited resistance to antibiotics such as cotrimoxazole, clindamycin, and vancomycin. Conclusion Both Septicidine and Betadine were effective in reducing hand bacterial load, although neither achieved complete sterilization. Alcohol-based solutions such as Septicidine may offer benefits in terms of ease of use and skin compatibility. Improving iodine-based solutions such as Betadine application techniques may enhance its efficacy. Further research is warranted to optimize hand hygiene protocols in surgical environments.